Stereoscopic 3D objects evoke stronger saliency for nonverbal working memory: An fMRI study. Issue 1 (March 2016) - Park, Jang‐Woo; Kim, Yang‐Tae; Yun, Byoung‐Ju; Jin, Sung‐Uk; Lee, Sang‐Hoon; Ahn, Shi‐Hyun; Min, Yusun; Jung, Tae‐Du; Lee, Hui Joong; Chang, Yongmin
ABSTRACT: Effective working memory (WM) training is often desired to improve WM. Recent studies have suggested that WM training is more successful when participants monitor scenes in three‐dimensional (3D) environments. Although previous neuroimaging studies have examined visuospatial WM in relation to a 3D scene or object, these studies did not investigate WM using stereoscopic 3D object stimuli. We used functional magnetic resonance imaging (fMRI) to identify brain activation during an N‐back task with 3D object stimuli, and determined the difference in activation pattern between stereoscopic versus shaded 3D objects. We found that the anterior insula, ventral striatum, and posterior orbitofrontal cortex showed greater activation during the 2‐back task with stereoscopic 3D objects than with shaded 3D objects. These regions have previously been associated with a salience network.